1998
DOI: 10.1139/t97-062
|View full text |Cite
|
Sign up to set email alerts
|

Horizontal deformation in reinforced soil walls

Abstract: The results of a numerical study of the horizontal deformations of reinforced soil walls with a continuous panel facing are presented. The most important material parameters are shown to be the reinforcement stiffness density and the backfill soil friction angle. The soil-facing interface friction angle, reinforcement-soil friction angle, soil Young's modulus, and facing rigidity are less important. For backfill soil having a friction angle greater than or equal to 35°, the common practice of using a truncated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 83 publications
(10 citation statements)
references
References 2 publications
0
10
0
Order By: Relevance
“…The survey by classified the numerical modelling attempts into two major groups on the basis of whether or not numerical results were compared with measurements from physical models, including field-instrumented walls. Many of the studies reviewed by the authors investigated the response of idealized reinforced soil wall models (e.g., Ho and Rowe 1996;Rowe and Ho 1998;Hatami et al 2001). Relatively fewer studies are available in the literature that report direct comparisons of numerical results and experimentally measured results from full-scale instrumented walls (e.g., Gotteland et al 1996Gotteland et al , 1997Karpurapu and Bathurst 1995;Ling et al 2000;Lopes et al 1994;Biondi et al 2000).…”
Section: Introductionmentioning
confidence: 99%
“…The survey by classified the numerical modelling attempts into two major groups on the basis of whether or not numerical results were compared with measurements from physical models, including field-instrumented walls. Many of the studies reviewed by the authors investigated the response of idealized reinforced soil wall models (e.g., Ho and Rowe 1996;Rowe and Ho 1998;Hatami et al 2001). Relatively fewer studies are available in the literature that report direct comparisons of numerical results and experimentally measured results from full-scale instrumented walls (e.g., Gotteland et al 1996Gotteland et al , 1997Karpurapu and Bathurst 1995;Ling et al 2000;Lopes et al 1994;Biondi et al 2000).…”
Section: Introductionmentioning
confidence: 99%
“…Another important aspect of reinforced earth numerical modeling is the use of an appropriate constitutive model to predict soil behavior. The literature indicated a number of case studies in which MSE walls were modeled using the elastic-plastic Mohr-Coulomb constitutive model that yielded satisfactory results (Bergado and Teerawattanasuk 2008;Reddy and Navarrete 2008;Kim et al 2010;Rowe and Ho 1998;Pierson et al 2011;Leshchinsky and Vulova 2001). Huang et al (2009) presented a study on segmental reinforced soil walls using modified Duncan-Chang, Lade, and Mohr-Coulomb constitutive models.…”
Section: Numerical Modeling Of Mse Wallmentioning
confidence: 99%
“…A previous study indicated that the variation in displacement was negligible for the reduction in interface angle from 1.0 to 0.67 of reinforced-fill friction (Rowe and Ho 1998). Therefore, interface friction between soil and reinforcement was considered to be 0.67 of the friction angle of reinforced backfill.…”
Section: Development Of Fe Modelmentioning
confidence: 99%
See 2 more Smart Citations